Estudo sobre os métodos de reciclagem e reutilização de baterias de lítio de carros elétricos - Ohtsuka, Rodrigo Seiji (Universidade Federal de São Carlos, 2022)
Electric vehicle (EV), means of transport considered more sustainable to the environment, have become popular around the world in recent years mainly in the United States, Europe and China. For the next decades, the volume of EVs is expected to grow exponentially, replacing large part of the fleet of vehicles with a combustion engine. Issues such the concerns about effects of global warming, government incentives to sell EVs, fast technological development, and optimization in lithium batteries (LiB) are among the main reasons for the expansion of this market. However, it is important to assess which environmental impacts and fate of the large number of LIBs that will be taken from EVs in the next years, in addition to the risk of lack of raw material to manufacture them (mainly lithium and cobalt). In this context, the purpose of this work emerged, whose objective was to carry out a study on the possible social and environmental effects of LiBs, and to discuss the main existing resources and methods to reuse and/or recycling it. After a extensive research in the literature about this topic, it was verified that the reuse (known as second-life use) and recycling through hydrometallurgy and pyrometallurgy will be necessary alternatives in the near future to mitigate the impacts on the environment and possible lack of supply of raw materials of lithium batteries. However, both processes must overcome some barriers to becoming viable on a large scale, mainly economic, making crucial the role of governments to help implement those processes.
Study on recycling methods and reuse of car´s lithium-based electrical batteries
Keywords: Baterias; Reciclagem; Litio; Batteries; Lithium; Recycling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO